Low Birth Weight as A Predictor of Stunting in Bojonegoro, East Java, Indonesia - Wiwik Utami; Aris Citra Wisuda; Titik Nuryanti; Siti Patonah; Ahmad Maftukhin; Novia Dwi Astuti; Agus Ari Affandi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Birth weight is the primary indicator of a baby's health. Babies with low body weight often face challenges in physical growth, metabolic function, and cognitive and intellectual development. The purpose of this study is to determine the relationship between a history of low birth weight and stunting. This study used a correlational analytical design with a cross-sectional approach. The population included 120 pairs of mothers and children aged 2–3 years. A simple random sampling technique selected 108 pairs as the sample. Data were collected by measuring the child's height and by obtaining secondary data on birth weight. Data analysis was carried out using Chi-Square and Contingency Coefficient tests. The results showed that of 69 respondents (63.9%) who had a history of low birth weight, as many as 45 children (41.7%) were stunted. The majority of respondents were children aged 2-3 years (92.3%), female, and firstborn. A chi-square statistical test yields a P-value = 0.008 < a (0.05). This indicates a relationship between a history of low birth weight and the incidence of stunting in children aged 2–3 years, with a Contingency Coefficient rate of 0.462. The conclusion shows that there is a link between low birth weight and the incidence of stunting in children aged 2–3 years. Parents are encouraged to attend Posyandu regularly for growth monitoring and optimal nutrition. Healthcare workers should prioritize nutritional counseling during pregnancy and the first two years of life. Policymakers are recommended to strengthen prenatal screening programs targeting low birth weight as an early predictor of stunting, particularly in agricultural communities with limited healthcare access. Keywords: Low Birth Weight, Stunting, Child Nutrition, Indonesia, Growth Disorders.